Serum vitamin D-binding protein is a third member of the albumin and alpha fetoprotein gene family. - Cooke, N E (1985)
A near full-length cDNA encoding the human vitamin D-binding protein (hDBP) was isolated from a human liver mRNA expression library. Complete sequence analysis of this clone predicts the full-length amino acid sequence of the pre-hDBP. Comparison of the sequence of the hDBP mRNA and protein to existing protein and nucleic acid data banks demonstrates a strong and highly characteristic homology of the hDBP with human albumin (hALB) and human alpha-fetoprotein (hAFP). Based upon this structural comparison, we establish that DBP is a member of the ALB and AFP gene family.